2021
DOI: 10.1093/cid/ciab933
|View full text |Cite
|
Sign up to set email alerts
|

The Removal of Airborne Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) and Other Microbial Bioaerosols by Air Filtration on Coronavirus Disease 2019 (COVID-19) Surge Units

Abstract: Airborne SARS-CoV-2 was detected in a COVID-19 ward before activation of portable HEPA-air filtration, but not during the week of filter operation; SARS-CoV-2 was again detected when the filter was off. Airborne SARS-CoV-2 was infrequently detected in a COVID-19 ICU. Filtration significantly reduced other microbial bioaerosols in both settings.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 11 publications
3
45
0
Order By: Relevance
“…This natural experimental study is the first of its kind to comprehensively evaluate both the sequential transport of airborne PM around a medical ward, and to assess the impact of air filtration devices on this. While we did not distinguish between bioaerosols and inert aerosols, the fact that viral particles tend to occur mostly in smaller respiratory aerosols <5 µm diameter [38-40] means that the behaviour of monitored PM signals is likely to have been indicative of any bioaerosols present in the ward air. As such, the study sheds new light on the transport of aerosols around hospital wards that might be helpful in better understanding the dynamics of airborne nosocomial transmission of viruses such as SARS-CoV-2 in clinical settings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This natural experimental study is the first of its kind to comprehensively evaluate both the sequential transport of airborne PM around a medical ward, and to assess the impact of air filtration devices on this. While we did not distinguish between bioaerosols and inert aerosols, the fact that viral particles tend to occur mostly in smaller respiratory aerosols <5 µm diameter [38-40] means that the behaviour of monitored PM signals is likely to have been indicative of any bioaerosols present in the ward air. As such, the study sheds new light on the transport of aerosols around hospital wards that might be helpful in better understanding the dynamics of airborne nosocomial transmission of viruses such as SARS-CoV-2 in clinical settings.…”
Section: Discussionmentioning
confidence: 99%
“…As the majority of airborne virus is thought to be contained in particles of <5 µm [39, 40, 49], the results reported here imply that appropriately sized and situated air filtration devices, supplementing ward ventilation, may have a significant impact on the nosocomial transmission of viral and other microbial infections. Interestingly, Conway-Morris et al [38] observed most viral particles to be in aerosol particles of 1-4 µm diameter, with some in aerosols >4 µm. As well as impacting in the nasopharynx, these smaller aerosols can travel deeper into the lungs to the alveolar level, and there is evidence that this may be associated with more severe disease [12, 13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, AGPs and contaminated air between rooms or open bay dental chairs could remain a source of contamination [ 34 , 35 ]. There is a growing body of evidence supporting the use of portable air filters [ 36 ] and air cleaners [ 7 ] as mitigating measures to help reduce such risk, however further dental aerosol studies sampling specifically for the virus are required. This study provides further evidence for sources of aerosol generation during common dental procedures, enabling a more holistic approach to risk assessment [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Alternative measures for protection against SARS-CoV-2 transmission through the air is the use of room air filtration systems. While evidence of transmission reduction with the use of air filters is anecdotal at best, it has been solidified that such systems can remove virus-containing particles from the air [27,28] . Still, it is quite clear, that such systems can only prevent the accumulation of infectious aerosols in closed rooms while direct transmission between persons also via aerosols is still very possible, and could even be enhanced when the airflow generated by the filter is drawing infectious aerosol towards s susceptible person before filtering it.…”
Section: Discussionmentioning
confidence: 99%